2021
DOI: 10.3390/ijms22094480
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Pharmacogenetic Studies in Patients with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is an important global public health problem due to its high prevalence and morbidity. Although the treatment of nephrology patients has changed considerably, ineffectiveness and side effects of medications represent a major issue. In an effort to elucidate the contribution of genetic variants located in several genes in the response to treatment of patients with CKD, we performed a systematic review and meta-analysis of all available pharmacogenetics studies. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Ethnic variation may influence individual responses to medications and susceptibility to specific health conditions associated with CKD. 50,51 The majority of studies in this review were conducted in Western countries. Although no distinct differences in the prevalence of IP across country settings were observed, ethnic factors might contribute to the observed incongruities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic variation may influence individual responses to medications and susceptibility to specific health conditions associated with CKD. 50,51 The majority of studies in this review were conducted in Western countries. Although no distinct differences in the prevalence of IP across country settings were observed, ethnic factors might contribute to the observed incongruities.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic variation may influence individual responses to medications and susceptibility to specific health conditions associated with CKD 50,51 . The majority of studies in this review were conducted in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in future, there may be a role for pharmacogenetics in mainstream practice around transplantation. 28 , 29 , 30 …”
Section: The Multidisciplinary Teammentioning
confidence: 99%
“…In addition, in future, there may be a role for pharmacogenetics in mainstream practice around transplantation. [28][29][30] A situation in which genetic testing should be considered in a potential kidney transplant recipient is when the etiology of the recipient's kidney disease is unclear. In this situation, the recipient should be phenotyped, with the genomic test using either exome sequencing (ES) or genome sequencing (GS).…”
Section: Indications Risks and Benefits Of Genetic Testingmentioning
confidence: 99%
“…Recent studies among some populations have confirmed that single nucleotide polymorphisms (SNPs) of ATP binding cassette gene B1 (ABCB1), nuclear receptor subfamily 3 group C member 1 gene (NR3C1), T-cell transcription factor encoding gene (TBX21) and vitamin D receptor encoding gene (VDR) are associated with steroid response. [5][6][7][8] NR3C1 gene encodes the glucocorticoid (GC) receptor, and studies suggested that the lower frequency of NR3C1 rs41423247 polymorphism might contribute to the decreased GC sensitivity in the hypothalamic-pituitaryadrenal (HPA) axis. 6,9 TBX21 gene encodes transcription factors involved in the regulation of developmental processes, including glucocorticoid receptor regulatory network.…”
Section: What Is Known and Objectivementioning
confidence: 99%